Adaptaciones curriculares para estudiantes con Trastorno por Déficit de Atención e Hiperactividad (TDAH) tipo inatento de Octavo Grado en la asignatura de Ciencias Naturales - Correa León, Kerly Melisa (2025)
Curricular adaptations are adjustments in different curriculum elements to address the special educational needs (SEN) of each student, in this case, those associated with Attention Deficit Hyperactivity Disorder (ADHD). The present research aims to propose curricular access and methodological adaptations by designing micro-curricular lesson plans for the teaching and learning of Natural Sciences in students with inattentive ADHD. Regarding the methodology, the inductive method was used through a bibliographic search focused on ADHD, to analyze the behavioral traits characteristic of individuals with this diagnosis. As for the approach, a qualitative perspective was adopted, as it allows for an in-depth examination of the particularities of the aforementioned disorder based on literature review and previous studies. From the bibliographic analysis carried out, it was possible to deepen the understanding of how attentional difficulties, impulsivity, and behavioral problems typical of ADHD affect the student's interaction with their school environment. Concerning the type of research, this falls within the documentary approach, since it is based on the collection and critical analysis of a variety of primary and secondary sources, such as scientific articles, specialized books, and other relevant materials. The purpose of this analysis is to deepen knowledge about ADHD and the pedagogical strategies related to its approach. Based on the results obtained through the research instruments applied to the specialist and the bibliographic analysis, the difficulties faced by students with ADHD were determined, as well as the most appropriate strategies for their learning. In this sense, the relevance of both curricular access and methodological adaptations is highlighted, to support the educational process of these students. Finally, it is concluded that, based on the actions developed in this research, it is feasible to implement curricular adaptations in lesson planning for students with inattentive ADHD. These adaptations can be applied in the subject of Natural Sciences for Eighth Year of Upper Basic General Education of the national education system, to optimize their learning process and promote a more inclusive educational environment